Failure of deactivation in the default mode network: a trait marker for schizophrenia?. Issue 6 (21st October 2014) - Landin-Romero, R.; McKenna, P. J.; Salgado-Pineda, P.; Sarró, S.; Aguirre, C.; Sarri, C.; Compte, A.; Bosque, C.; Blanch, J.; Salvador, R.; Pomarol-Clotet, E.
Abstract : Background: Functional imaging studies in relatives of schizophrenic patients have had inconsistent findings, particularly with respect to altered dorsolateral prefrontal cortex activation. Some recent studies have also suggested that failure of deactivation may be seen. Method: A total of 28 patients with schizophrenia, 28 of their siblings and 56 healthy controls underwent functional magnetic resonance imaging during performance of the n-back working memory task. An analysis of variance was fitted to individual whole-brain maps from each set of patient–relative–matched pair of controls. Clusters of significant difference among the groups were then used as regions of interest to compare mean activations and deactivations among the groups. Results: In all, five clusters of significant differences were found. The schizophrenic patients, but not the relatives, showed reduced activation compared with the controls in the lateral frontal cortex bilaterally, the left basal ganglia and the cerebellum. In contrast, both the patients and the relatives showed significant failure of deactivation compared with the healthy controls in the medial frontal cortex, with the relatives also showing less failure than the patients. Failure of deactivation was not associated with schizotypy scores or presence of psychotic-like experiences in the relatives. Conclusions: Both schizophrenic patients and their relatives show altered task-related deactivation in the medial frontal cortex. This in turn suggests that default mode network dysfunction may function as a trait marker for schizophrenia.